Histamine receptors in GtoPdb v.2021.3. (2021) - Chazot, Paul; Cowart, Marlon; Fukui, Hiroyuki; Ganellin, C. Robin; Gutzmer, Ralf; Haas, Helmut L.; Hill, Stephen J.; Hills, Rebecca; Leurs, Rob; Levi, Roberto; Liu, Steve; Panula, Pertti; et al.
No abstract available